Pregnant and lactating women's knowledge of exclusive breastfeeding - Ana Paula Pessoa Maciel; Ana Paula Soares Gondim; Ana Martins Vieira da Silva; Fernando Colares Barros; Gizelle de Lima Barbosa; Keylla Conceição de Albuquerque; Lucas de Lavôr Rios; Maria Socorro Vieira Lopes; Silézia Maria Franklin de Souza (Universidade de Fortaleza, 2014)
Objective: To identify what pregnant and lactating women say about what is exclusivevbreastfeeding, its duration and benefits for moms and babies. Methods: This is a quantitative,descriptive study that took place in 2011 at a Family Health Center in Fortaleza-CE. The following variables were analyzed: socioeconomic characteristics, knowledge and attitude regarding breastfeeding and its benefits for the mom and baby. Data collection was performed using a questionnaire and consisted of a non-probability sample of 45 women with simple descriptive statistical analysis using proportion. Results: In all, 40 (88.9%) respondents were pregnant and 5 (11.1%) were breastfeeding. Mean age was 24 years. Regarding socioeconomic characteristics, 12 (30%) women said they were housemaids, 9 (22.5%) were housewives and 6 (15%) were unemployed. Concerning the definition of exclusive breastfeeding, 25 (55.6%) women considered breast milk as the only form of breastfeeding, five (11.1%) respondents considered breast milk, water and tea and 12 (26.7%) women did not know the meaning of the term. Considering the benefits, 16 (35.7%) women reported the strengthening of the bond with the child. Conclusion: It was observed that the assessed moms had knowledge of the definition, duration and benefits of exclusive breastfeeding; however, they presented some factors that contributed to early weaning. doi:10.5020/18061230.2013.p311